PERAN PETUGAS KESEHATAN TERHADAP KONSUMSI GARAM BERIODIUM PADA KELUARGA DI DESA SUNGAI KAPAS: THE ROLE OF HEALTH OFFICER ON COMSUMPTION IOUDIUM SALT ON FAMILY IN SUNGAI KAPAS VILLAGE - Filius Chandra; Tina Yuli Fatmawati; Sri Rahayu Ariza (Jurnal Psikologi Jambi, 2019)
Introduction: The state of good nutrition is a major prerequisite in realizing a healthy and quality of human resources. Iodine deficiency is a global health problem affecting more than 50 countries in the world. A third of the world's population suffers from iodine deficiency, including school children from mild to severe iodine deficiency.Method: method this research is quantitative with cross sectional study design that aims to see the relationship between nutritional knowledge and the role of health officers effects to consumption of iodized salt in sungai kapas village of bangko subdistrict. Population of this research is 1,908 households with the number of samples in detail for 91 households in the river kapas village of bangko merangin district. The data were collected by using questionnaire instrument and salt inspection using iodine test. Sampling process using proportional random sampling method by univariate analysis and bivariate analysis with chi-square test.Result: Results the results of study are while for 91 respondents majority 57 (62,6%) that health worker have good role and the rest 34 of respondent(37,4%) saynot. The result of p-value = 0,005 (p <0,05). It can be concluded that there is a significant correlation the role of health officer with iodized salt consumption at household in sungai kapas village.Conclusion and Recommendation: Conclusion is hope that housewives can choose iodized salt and can store salt properly so that family members can avoid iodine deficiency. Keywords: Iodized Salt Consumption, The Role Of Health Personnel